Blastocystis sp. Subtypes Colonisation and their Association with Clinical Diseases: A Systematic Review - Nurul Saadah Mohd Shaari; Mohd Rahman Omar; Ii Li, Lee; Wan Shahida Wan Sulaiman; Nadeeya'ayn Umaisara Mohamad Nor; Noradilah Samseh Abdullah (Akademi Sains Malaysia, 2024)
Indexed by SCOPUS/MYCITE